Review of Walter Scheidel's the great leveler: Violence and the history of inequality from the stone age to the twenty-first century - Easterly, William (Journal of Economic Literature)
The Great Leveler: Violence and the History of Inequality from the Stone Age to the Twenty-first Century's thesis is that violence and only violence significantly reduces inequality. It shows supportive cases of violence reducing inequality, especially World War II and the Russian and Chinese Revolutions, and highlights recent peacetime increases in within-country inequality. The great virtue of the book is to present a lot of evidence on both sides for the readers to judge the thesis for themselves. Other historical evidence is not supportive. Other measures of inequality, like absolute poverty or inequality between countries or groups, show many examples of violence making inequality or deprivation worse. The unequal burden of conscription, rationing, and casualties may also show war to be dis-equalizing. Also against the thesis is that recent peaceful globalization of trade, investment, and migration flows, including the rapid growth of China and India, has arguably reduced global inequality and absolute poverty to a historic extent. - Reproduced
Keywords: Inequality